Écrire les expressions suivantes sous forme de puissance :
D=2*2*2*(-2) ; E=3*(-3)*(-3) ; F=4*16*4*64 ; G=(-5)*25*125/5*(-25)

2
^ se lit puissance
D = 2*2*2*(-2)
D = -(2^4)

E = 3*(-3)*(-3)
E = 3^3

F = 4*16*4*64 or
4 = 2*2
16 = 4*4 = 2*2 * 2*2
64 = 16*4 = 2*2 * 2*2 * 2*2
F = (2*2) * (2*2 * 2*2) * (2*2) * (2*2 * 2*2 * 2*2) = 2^14

G = (-5)*25*125/5*(-25)
25 = 5*5
125 = 25*5 = 5*5*5

G = (-5)*(5*5)*(5*5*5)/5*(-5*5)
G = (-5)*(5*5)*(5*5*)*(-5*5)
G = 5^7
Merci :)
De rien :)

Réponses

2014-04-03T22:14:20+02:00
2014-04-03T22:19:08+02:00